Effectiveness of antibiotic treatment in children with Lyme neuroborreliosis - a retrospective study - Sigurdur Arnason; Barbro H. Skogman (BMC Pediatrics, 2022)
Abstract Background Lyme neuroborreliosis (LNB) is a tick-borne infection caused by the spirochete Borrelia burgdorferi sensu lato complex with various neurological manifestations. The recommended treatment for LNB in Swedish children has been intravenous ceftriaxone 50–100 mg/kg × 1 (< 8 years of age) or oral doxycycline 4 mg/kg × 1 (≥ 8 years of age) for 10–14 days. Studies on adult LNB patients have shown equal efficacy for ceftriaxone and doxycycline, but no such studies have been conducted on pediatric LNB patients. The aim of this study is to retrospectively evaluate clinical outcome in children with LNB who have received intravenous ceftriaxone or oral doxycycline. Results Clinical and laboratory data from three previously conducted prospective studies on children with LNB (1998–2014) were retrospectively analyzed. A total of 321 children (1–19 years of age), who received antibiotic treatment for definite LNB or possible LNB, were included. Clinical outcome at the 2-month follow-up (recovery/non-recovery) was evaluated using Chi2 test and logistic multivariate regression analysis. Out of 321 LNB patients, 194 children (60%) had received ceftriaxone and 127 children (40%) had received doxycycline. When comparing clinical outcome between treatment groups, no difference was found (p = 0,217). Results did not change when incorporating relevant clinical and laboratory data into the logistic multivariate regression analysis. Conclusion In this large retrospective study, no difference in clinical outcome was found, independent of age, when comparing children who received ceftriaxone with those who received doxycycline, supporting an equal effectiveness for treatment of LNB pediatric patients. However, future randomized comparative treatment studies are warranted for evaluation of efficacy of antibiotic treatment in pediatric LNB patients.